Competitive Strategy Orientations of Small and Medium Business Owners and their Performance Impacts: The Case of Paint Manufacturing SMEs in South-Western Nigeria - Oyedijo, Ade (Journal of Asian Business Strategy, 2012)
This paper outlines the results of a study of the competitive strategy orientations of 92 small and medium sized paint manufacturing enterprises in Southwestern Nigeria. Three sets of paint manufacturing SMEs which had substantially divergent competitive strategies, i.e. Differentiation (28) Low cost (33) and mixed strategies (31) were identified and compared using data generated through a survey. The data analysis using correlation matrix and simple linear regression reveals a highly significant impact of the three strategies on the performance of the sampled firms. Results of the analysis revealed a significant difference between the performance of companies that used differentiation and low cost as standalone strategies and the performance of firms that used the two strategies together. Those using mixed strategies performed better than those using stand alone strategies on all the three performance parameters of total income/revenue growth, sales growth and customer complaints. A possible explanation for this result is the flexibility which the combined use of the two strategies introduces into the operation of the firms that adopted this dual approach.